STRUKTUR DAN KOMPOSISI JENIS VEGETASI PENYUSUN HUTAN RAKYAT DI DUSUN KALIMENDONG KECAMATAN LEKSONO KABUPATEN WONOSOBO - , AGUS SUWITO AJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest is one of the areas where the resources are able to provide for the needs of living things, ranging from the need for food, life and the fulfillment necessary most important and can not be met by other resources as the forest is the largest provider of oxygen used for breathing creatures. But lately dwindling forests that because the population is increasing public demand for land that is increasing as well so that sustainability needs to be considered. This study aimed to determine (1) the composition of the forest and the people in the village constituent Kalimendong, (2) Knowing the people in the village forest structure Kalimendong, (3) Knowing IVI each type of constituent community forest in the village of Kalimendong at various stages of growth. This study was done in Kalimendong Hamlet, Village Kalimendong, Leksono Subdistrict, Wonosobo regency, Central Java. The method used is to create a Nested Sampling size of 20x20 meters by 30 plots were randomly assigned to the data height, diameter, crown width, and tree species. Results of research and analysis at the study site was found 16 species of plants, among others, avocado, resin, durian, ganetri, teak, coffee, lamtoro, mahogany, melinjo, Mindi, jackfruit, banana, flower, sengon, Suren and hibiscus. People in the village forest structure kalimendong layered and quite evenly spreading the average number of seedlings 7833.3 / ha, sapling 1533.3 / ha, 713.3 pole / ha and tree 150/Ha .. highest importance value index the village is dominated by sengon kalimendong with levels (124.4% seedling, sapling 166.6%, 193.1% pole, tree 170.8%) followed suren and other types.